Global Distribution Patterns of Carbapenemase-Encoding Bacteria in a New Light: Clues on a Role for Ethnicity - Neidhöfer, Claudio; Buechler, Christian; Neidhöfer, Guido; Bierbaum, Gabriele; Hannet, Irene; Hoerauf, Achim; Parčina, Marijo (Frontiers in Cellular and Infection Microbiology, 2021)
Antibiotic resistance represents a major global concern. The rapid spread of opportunistically pathogenic carbapenemase-encoding bacteria (CEB) requires clinicians, researchers, and policy-makers to swiftly find solutions to reduce transmission rates and the associated health burden. Epidemiological data is key to planning control measures. Our study aims to contribute by providing an analysis of 397 unique CEB isolates detected in a tertiary hospital in Germany. We propose new findings on demographic variables to support preventive sanitary precautions in routine clinical practice. Data on detected CEB was combined with patient’s demographic and clinical information for each isolate. Multiple regression techniques were applied to estimate the predictive quality of observed differences. Our findings confirm the role of age and gender in CEB colonization patterns and indicate a role for ethnicity and domicile. Also, carbapenemase-encoding A. baumannii was most frequently introduced to the hospital, while the risk of colonization with VIM-encoding P. aeruginosa rose with the length of hospital stay. P. aeruginosa remains an important complication of prolonged hospital stays. The strong link to hospital-wastewater may have implications for hospital-built environments. A. baumannii can be efficiently controlled from spreading at hospital admission. OXA-encoding CEB being harder to detect in routine screening, targeted preventive measures, such as culture media selective for carbapenem-resistant bacteria, would be opportune for patients from selected regions. The CEB differences linked to ethnicity found in our study may further be supporting the tailoring of diagnostic approaches, as well as health policies upon confirmation by other studies and a better understanding of their global distribution.